Remembering Soviet Food Culture: Experiences of a Memory Community in Estonia - Bardone, Ester; Kannike, Anu (Food & History, 2020)
Abstract The article contributes to the life history and narrative research on collective memory, addressing how the food culture of mature socialism in Estonia was remembered by a particular memory community (people born in the 1920s-1940s) in the postsocialist situation (early 2000s). Both pre-war society in the independent Republic of Estonia and the postsocialist era became the lenses through which food practices of Soviet Estonia were interpreted. These memories shed light on some nationally specific ways of remembering Soviet food culture, most clearly expressed in seeing the continuity of pre-WWII practices and in symbolic distinctions between “our” and “their” food culture. The study also demonstrates how memory institutions (Estonian National Museum, Estonian Literary Museum) have influenced the ways of remembering as well as the structure and content of memories. Abstract Cet article contribue à l’histoire de vies et à la recherche narrative sur la mémoire collective. Il explore comment une communauté de mémoire (personnes nées entre 1920 et 1940) dans le contexte postsocialiste du début des années 2000 s’est souvenue de la culture alimentaire du socialisme mature en Estonie. La société d’avant-guerre dans la République d’Estonie indépendante et l’ère postsocialiste sont devenues les prismes par lesquels les pratiques alimentaires de l’Estonie soviétique sont interprétées. Ces souvenirs mettent en lumière des caractéristiques nationales de se souvenir de la culture alimentaire soviétique, clairement exprimées par la continuité des pratiques antérieures à la seconde guerre mondiale et les distinctions symboliques entre “notre” et “leur” culture alimentaire. L’étude montre également comment les institutions mémorielles (Musée national estonien, Musée littéraire estonien) ont influencé les façons de se souvenir ainsi que la structure et le contenu de ces souvenirs.